Factors influencing duiker dung decay in north-east Gabon: are dung beetles hiding duikers? - Vliet, N. van; Nasi, Robert; Lumaret, J.P. (Wiley, 2009)
We analysed seasonality of dung decay time and the influence of rainfall, leaf fall, beetle attack and moisture on dung decay. Our study was carried out at the Ipassa Reserve, north-east Gabon. We compared the seasonality of dung decay with the seasonality of dung beetle abundance and guild structure. Dung beetle activity was the main factor influencing dung decay in our study site. Decay time was the highest during the main dry season (3.4 days) and the lowest during the short rainy season (0.7 days). Dung decay time was closely related to dung beetle abundance, especially to the abundance of nocturnal beetles. We discuss the implications of such results for duiker survey methods based on dung pellet counts in areas where decay time is extremely short or unknown.